2016
DOI: 10.18294/sc.2016.912
|View full text |Cite
|
Sign up to set email alerts
|

Acceso a servicios de salud dental en menores de doce años en Perú, 2014

Abstract: The aim of the study was to explore the patterns of dental health services access in children under twelve years of age in Peru. Data from 25,285 children under 12 years who participated in the Demographic and Family Health Survey of 2014 were reviewed. An exploratory spatial analysis was performed to project the proportions of children with access to dental health services, according to national regions, type of health service and urban or rural place of residence. The results show that of the total sample, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
4
0
5
Order By: Relevance
“…We identified that the region with the highest probability of access to oral health services for children was the Peruvian highlands. These findings reinforce those of another study 24 where the frequency of access to oral health services was higher in the Peruvian highlands than in coastal or jungle regions. This result corresponds to the regions where the JUNTOS program has been in place the longest according to its performance report ( http://goo.gl/9psqai ).…”
Section: Discussionsupporting
confidence: 90%
“…We identified that the region with the highest probability of access to oral health services for children was the Peruvian highlands. These findings reinforce those of another study 24 where the frequency of access to oral health services was higher in the Peruvian highlands than in coastal or jungle regions. This result corresponds to the regions where the JUNTOS program has been in place the longest according to its performance report ( http://goo.gl/9psqai ).…”
Section: Discussionsupporting
confidence: 90%
“…Según la OMS la caries logra afectar entre el 60 % y 90 % de la población escolar y su aparición se asocia con factores socioculturales, económicos, ambientales y del comportamiento (Cerón-Bastidas, 2015;Corrêa-Faria et al, 2016). Otro factor que influye son las barreras para recibir tratamiento dental adecuado: barreras de acceso y utilización de servicios odontológicos (Hernández-Vásquez et al, 2016), donde los factores económicos influyen en el acceso a los servicios de salud y la capacidad de los individuos para obtener cobertura (Palomer Roggerone, 2016).…”
Section: Introductionunclassified
“…Peruvian 2014 Demographic and Health Survey (DHS) showed a rather discouraging outlook concerning the oral health services utilization, where only 22% of the elderly attended any dental health service [7]. Furthermore, only 27% of children under 12 years used any dental service in the previous 6 months prior to the survey [8]. Percentage of utilization in both groups are low taking in account the at least 2 visits per year internationally accepted recommendation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Percentage of utilization in both groups are low taking in account the at least 2 visits per year internationally accepted recommendation [9]. Additionally, studies show important inequalities in the oral health services utilization by many other characteristics like type of health insurance, residency region and urban or rural setting [7, 8]. These findings show a problem of great magnitude that needs to be analyzed and addressed by decision makers and health researchers to shorten the inequality gaps in Peru.…”
Section: Introductionmentioning
confidence: 99%